7cos(4x-1)-3=0

Simple and best practice solution for 7cos(4x-1)-3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7cos(4x-1)-3=0 equation:


Simplifying
7cos(4x + -1) + -3 = 0

Reorder the terms:
7cos(-1 + 4x) + -3 = 0
(-1 * 7cos + 4x * 7cos) + -3 = 0
(-7cos + 28cosx) + -3 = 0

Reorder the terms:
-3 + -7cos + 28cosx = 0

Solving
-3 + -7cos + 28cosx = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + -7cos + 3 + 28cosx = 0 + 3

Reorder the terms:
-3 + 3 + -7cos + 28cosx = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -7cos + 28cosx = 0 + 3
-7cos + 28cosx = 0 + 3

Combine like terms: 0 + 3 = 3
-7cos + 28cosx = 3

Reorder the terms:
-3 + -7cos + 28cosx = 3 + -3

Combine like terms: 3 + -3 = 0
-3 + -7cos + 28cosx = 0

The solution to this equation could not be determined.

See similar equations:

| 1.5x+5=-0.5x-3 | | =2ab+3ba | | a-1=2a-7 | | xy+2x=13-4y | | 0*6-12/3-1 | | 3x-(10x-((9-30x+25x^2)-8)+(5x-3)(5x+4))=3(6x^2-4)-9(3x+(2x-1)(x-3)) | | 1-2a=49 | | 5x-0.5=0.5-5x | | 4.7+2.7= | | 4u+2.7= | | 2q^2-8q+50=0 | | x+9=x+2 | | x=100-2p | | 4/9×5/20 | | 5(2-C)=2(2x-13) | | 2x+125=0 | | 5x+7y=-41 | | 70=5x+13+3x+33 | | (x-15)(x+8)= | | 10-7t-19=7t+31-4t | | 4x-5=5+x | | 3+n=39-2n | | 5/12X5 | | 18(y-1)+12y=-8 | | 3(m-2)=6(m+4)-6 | | 5(2y+1)+7(4y+2)=0 | | 5sinx+12cosx-13=y | | m^3+8m-1=0 | | -50x^2+13=42x-39 | | 5+7y=2x+6+6y | | 4(8-5y)+2y=-40 | | 1(5x)-3=1 |

Equations solver categories